LACVD growth of diamond on gallium nitride substrates with PH3 in recipe - Awadesh Kumar Mallik; Awadesh Kumar Mallik; Awadesh Kumar Mallik; Kamatchi Jothiramalingam Sankaran; Kamatchi Jothiramalingam Sankaran; Kamatchi Jothiramalingam Sankaran; Derese Desta; Derese Desta; Paulius Pobedinskas; Paulius Pobedinskas; Rani Mary Joy; Rani Mary Joy; et al. (Frontiers in Energy Research)
Integrating chemical vapour deposition (CVD) diamond with GaN material for effective thermal management of the power electronic devices is critical. However, there are issues with CVD processing, like GaN substrate etching under normal CVD diamond growth conditions, which nowadays, is overcome by inserting an intermediate silicon nitride layer of very low thermal conductivity. Unfortunately, such a buffer layer is detrimental to proper heat dissipation. So, the direct growth of diamonds onto GaN substrates is still a relevant research topic. Here, we have used an innovative low-temperature growth process by linear antenna microwave plasma enhanced CVD to overcome such a problem. Other than the normal hydrogen gas CVD recipe, PH3 gas diluted with hydrogen (1,000 ppm in H2) was added as a doping gas precursor, to dope the diamond lattice with phosphorous atoms, by varying the substrate temperature from 400oC to 900oC. PH3 addition in the precursor gas recipe was found to etch the GaN substrate substantially. The phosphorous atom was found to be present on the surface of the diamond film from their corresponding X-ray photoelectron spectroscopy signal. Raman spectroscopy and scanning electron microscopy images do not reveal GaN substrate damage when pure hydrogen gas was used as a precursor without PH3 addition. However, there is a relative competition between the GaN substrate decomposition and CVD diamond growth rates when diluted PH3 gas was used in the precursor gas recipe. At a lower substrate temperature of 400oC, GaN etching was prevalent, but with a gradual increase in substrate temperature to 900ºC, diamond lateral growth was promoted inside the linear antenna CVD reactor, which partially protected the underneath GaN/sapphire heterostructures from decomposition under harsh plasma CVD conditions.